Higher fitness and competitive advantage of Pyricularia oryzae Triticum lineage resistant to QoI fungicides. Issue 12 (12th September 2022) - Dorigan, Adriano Francis; Moreira, Silvino Intra; Ceresini, Paulo Cezar; Pozza, Edson Ampélio; Belan, Leônidas Leoni; da Silveira, Patricia Ricardino; Alves, Eduardo
Abstract: Background: Quinone outside inhibitor (QoI) fungicides have not been effective in controlling the wheat blast disease [ Pyricularia oryzae Triticum lineage (PoTl)] in Brazil. The first report of resistance of PoTl to QoIs in this country occurred in 2015. This study aimed to test hypotheses about the changes in fitness parameters and competitive advantage of the QoI‐resistant (R) PoTl isolate group compared to the sensitive (S) isolate group. Mycelial growth on PDA medium and in vivo conidial production, incubation period and disease severity were analyzed as fitness parameters. The competitive ability was measured on wheat leaves and heads inoculated with mixtures of R:S isolates at the following proportions: 0S:100R, 20S:80R, 50S:50R, 80S:20R, 100S:0R, and 0S:0R. Results: The QoI‐R isolate group had significantly higher fitness than the sensitive isolate group, considering both in vitro and in vivo parameters. The highest in vivo conidial production on wheat leaves and the highest leaf and head disease severity were detected when resistant strains were predominant in the isolate's mixtures (20S:80R or 0S:100R proportions), in the absence of fungicide pressure. Conidia harvested from wheat blast lesions on leaves inoculated with 20S:80R and 0S:100R mixtures were resistant to QoIs in vitro assays based on discriminatory doses of the fungicide. Conclusion: Therefore, QoI resistance facilitated a higher fitness and a competitive advantage in PoTl, which contrasts with the evolutionary theory that associates a fitness cost to fungicide resistance. We discuss the evolutionary and ecological implications of the higher fitness as found in the fungicide‐resistant adapted populations of the wheat blast pathogen. © 2022 Society of Chemical Industry. Abstract :